The Guarantee of Children's Right in Determinating Guardian ad Litem on Sale and Purchase of Inherited Property - Rahmadanti, Saumita Ngesti; Marisa Kurnianingsih; Ellya Nur Fariesha Binti Azrurahime (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
On selling the property of minors, absolutely parents must pay attention to the main objective, namely the welfare of the child. Thus, it is not used for personal interests and overrides the interests of children because this is contrary to children's rights. This study examines protecting children's rights for Guardian ad Litem (GAL), which will trade their children's property. To study the rules governing how a guardian ad litem can handle inherited property for the benefit of minors because he is considered an heir to his parent's property if his parents die. This study uses an empirical juridical methodology from the legislative framework, cases, conceptual frameworks, and interviews. Then, the novelty contains the role of the government in regulating minors who legally sell their inherited property and consider related children's rights. The study shows that Badan Pertanahan Nasional (BPN) of Kota Surakarta has carried out its duties effectively, supported by the conditions set for parents who want to sell the property on behalf of their children. The results of this study are the steps taken by the government to ensure that parents do not abuse their power to steal children's property and further examine guardian ad litem ship according to Islamic law. The role of BPN of Kota Surakarta is also in collaboration with the Religious Court in charge of determining guardian ad litem of minors. It can be concluded that the reasons for parents who want to sell their children's inheritance are clear and not abused by parents who want to become guardian ad litem. It caused the role of guardian ad litem in Islam to include the maintenance of themselves and their property. So that all guardians ad litem maintain health, justice, honesty, and good behavior.